Analisis Model Peramalan Status Kredit Kendaraan Bermotor pada Astra Credit Companies (ACC) Cabang X Periode 2011 - Soemapradja, Tomy G.; Susanto, Prycillia (Binus Business Review, 2012)
In order to increasing revenue, credit and financial institution, especially, automotive financing, gave lower interest rate. This, of course, will impact to the costumer with higher opportunity to have their dream which facilitated by those institutions. Despites to all economic risks and sales targets, credit and financial institutions have to empower their credit monitoring to anticipate earlier of credit defaults. Inspired by Altmanâs research in 1968, about predicting bankruptcy of US companies, this research has purpose to determine which variable that significantly to the car loan status at Astra Credit Companies (ACC), and further continue to arrange prediction model of loan status and measure itâs accuracy level.. The statistic test shows there are 2 independent variables affect to dependent variable significantly, where modelâs accuracy level achieves 100%.